RELIGIOUS-RATIONAL INTEGRATION IN ISLAMIC EDUCATION: A STUDY OF THE THOUGHTS OF H.M. ARIFIN - Rendi Sabana; Maragustam Siregar (Yayasan Haiah Nusratul Islam, 2025)
This study aims to explore H.M. Arifin's thoughts on the integration of religious and rational values in Islamic education, as well as its application in modern education curriculum. Using a qualitative approach and literature study method, this research analyzes H.M. Arifin's works that outline the concept of education that not only prioritizes religious aspects, but also encourages critical and rational intellectual development among students. The findings show that this integration is very important in forming a generation that not only understands religion textually, but can also adapt to the development of science and technology. The religious-rational concept developed by Arifin contributes to the formation of individuals who have a balance between spirituality and intellectuality, and are able to face the challenges of an increasingly complex era. In addition, content analysis is used to find insights in the text or related visual data, while theoretical reflection and critical analysis strengthen a comprehensive understanding of the phenomenon under study. This research reveals that the religious-rational approach has the potential to overcome the gap between religious and general knowledge that often occurs in Islamic educational institutions. This is expected to help form a generation that has a solid spiritual and intellectual balance, and is able to compete in the era of globalization without losing its Islamic identity. In Indonesia, the context of Islamic education faces considerable challenges, as many institutions separate religious and scientific knowledge, thus creating a gap in the way students understand religion and think critically. Therefore, the results of this study are also expected to provide strategic recommendations for Islamic education institutions in Indonesia to face the demands of the modern era. Through a religious-rational approach, educational institutions can integrate the value of faith with science, so that students not only excel in religious matters but also have critical thinking skills and abilities that are relevant in an increasingly complex multicultural society.